Efeito do resveratrol e do alendronato de sódio na periodontite experimental: estudo piloto - Brito, Marina Araujo (2019)
Periodontitis is a chronic disease of multifactorial origin, which involves the periodontium of sustentation, being characterized by the presence of reabsorption of the alveolar bone. This disease is induced by an imbalance between bacterial virulence and host defenses, resulting in the destruction of periodontal tissues. The objective of this pilot study was to investigate the effect of resveratrol (RESV) and sodium alendronate (ALEN) on induced periodontitis in an animal model. For induction of periodontitis, ligatures were inserted into the second mandibular second molar and injected with Porphyromonas gingivalis. Treatment of periodontal disease was performed for 30 consecutive days orally (intragastric gavage). The animals were divided into three groups: RESV: 10 mg / kg Resveratrol; ALEN: 2 mg / kg of sodium alendronate and SHAM: control without medication. In order to evaluate bone resorption, radiographic, histological and immunohistochemical analyzes were performed for the proteins osteoprotegerin (OPG) and bone morphogenetic protein (rhBMP-2). The gene expression for Tnfα was also analyzed by the polymerase chain reaction (q-PCR). At the radiographic examination, less bone reabsorption was verified by measurement of the enamel-cement junction to alveolar bone crest in the ALEN group compared to the RESV and SHAM groups. For histometric analysis of the furcation area and interproximal measurement, lower reabsorption was demonstrated for the ALEN group. The rhBMP-2 and OPG proteins were more evident for the ALEN group. A high expression of the Tnfα gene was observed in the ALEN group compared to the RESV and SHAM groups. The present pilot study presented a favorable study design for future research protocols, helping to plan studies with greater sampling.